Study regarding the size and profile of farm holdings - Alexandra Marina Bratulescu (Manolache) (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
Agricultural land and other agricultural production resources are distributed on farms of different types and shapes. They also differ in the size of the resources held, with special reference to the area and / or the number of animals. The production results depend, of course, on the volume of resources, as well as on the way in which they are valued, although their low degree of concentration, in the case of family farms, makes the exploitation process more difficult. This paper is based on the analysis of statistical data from a quantitative and qualitative point of view, highlighting the determination of the degree of uniformity, the number of agricultural holdings and their size at regional level.
Keywords: A10; Q10; 330; agricultural holdings; size; area; regional